Shadow Epitaxy: Shadow Epitaxy for In Situ Growth of Generic Semiconductor/Superconductor Hybrids (Adv. Mater. 23/2020). Issue 23 (10th June 2020) - Carrad, Damon J.; Bjergfelt, Martin; Kanne, Thomas; Aagesen, Martin; Krizek, Filip; Fiordaliso, Elisabetta M.; Johnson, Erik; Nygård, Jesper; Jespersen, Thomas Sand
Abstract : In article number 1908411, Jesper Nygård, Thomas Sand Jespersen, and co‐workers present "shadow epitaxy", a novel method for controlled in situ growth of patterned metal/semiconductor hybrid nanostructures. The method enables exploration of material combinations previously unaccessible for epitaxial hybrid quantum devices. When applied to conventional materials the bottom‐up patterning significantly improves the electrical stability and reproducibility of quantum devices.